2016
DOI: 10.5812/ircmj.42360
|View full text |Cite
|
Sign up to set email alerts
|

MiR-328 May be Considered as an Oncogene in Human Invasive Breast Carcinoma

Abstract: BackgroundThe recent investigations have rendered microRNAs (miRs) as a novel biomarker in cancer research. In fact, alteration in miR expression may be associated with tumor suppression, tumorigenesis, metastasis, and poor prognosis in human breast cancer (BC).ObjectivesThe aim of this clinical experimental study was to measure the miR-328 expression level in breast cancer tissues, at first. Then, we tried to find out any possible correlation between miR-328 and prognostic and predictive biomarkers in BC. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…By contrast, DIO3OS promoted cell proliferation and invasion through competing for miR-122 to upregulate ALDOA expression in pancreatic cancer. 24 A plethora of researches on miR-328 have paid much attention to its functions on cell growth, invasion and migration in cancers, including gastric cancer, 25 invasive breast cancer, 26 non-small cell lung cancer, 27 and most importantly, HCC. 28 Additionally, overexpression of metastasis associated in lung adenocarcinoma transcript-1 sequestered cytoplasmic miR-328-3p, culminating in insulin-like growth factor 1 receptor induction to mediate hypoxia-stimulated proliferation of pulmonary artery smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, DIO3OS promoted cell proliferation and invasion through competing for miR-122 to upregulate ALDOA expression in pancreatic cancer. 24 A plethora of researches on miR-328 have paid much attention to its functions on cell growth, invasion and migration in cancers, including gastric cancer, 25 invasive breast cancer, 26 non-small cell lung cancer, 27 and most importantly, HCC. 28 Additionally, overexpression of metastasis associated in lung adenocarcinoma transcript-1 sequestered cytoplasmic miR-328-3p, culminating in insulin-like growth factor 1 receptor induction to mediate hypoxia-stimulated proliferation of pulmonary artery smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…One of the 28 miRNAs, miR-328, is involved in cancer [ 70 , 71 ], autoimmune [ 72 ], and neuronal diseases [ 73 ]. Tay et al demonstrated another role of miR-328 in the regulation of innate immune cell function by showing that suppression of miR-328 improved bacterial clearance in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth studies on the regulatory networks of miRNAs in cancer may provide novel prognostic predictors and therapeutic approaches, beneficial for patients with cancer (10). miR-328 has been reported to promote the progression of various cancer types, including breast and hepatocellular cancers (11,12). In NSCLC, elevations in miR-328 expression levels were associated with brain metastasis (13); however, the role of miR-328 in the development of cisplatin resistance in NSCLC remains unclear.…”
Section: Introductionmentioning
confidence: 99%